Efficiency of Wastewater Discharge Sanctions Discharges in Michoacán, México (2022). A Study Using Data Envelopment Analysis (DEA) with the Presence of Bad Outputs - Zamora Torres, América Ivonne (2025)
The objective of this study is to calculate the efficiency level of the sanctions for wastewater discharges implemented by CONAGUA in the state of Michoacán during fiscal year 2022, using Data Envelopment Analysis (DEA). This research is motivated by the high level of pollution generated by industrial and urban public activities, which casts doubt on the effectiveness of the coercive mechanism established by the current National Water Law. The analysis was conducted under variable returns to scale, input orientation, and with the presence of bad outputs. The results show that Michoacán is positioned at an intermediate efficiency level, highlighting areas for improvement to achieve a lower percentage of water that fails to meet the Mexican official standards, alongside an increase in the volume of good-quality water in surface receiving bodies.